Study of DNA interactions with melphalan, busulphan, and analogues using an HPLC method - Karikas, A.; Constantinou-Kokotou, V.; Magrioti, V.; Kokotos, G. (Journal of Liquid Chromatography and Related Technologies, 2000)
A simple reversed phase HPLC method suitable to study the interactions of alkylating agents with DNA is presented in this paper. DNA interaction is expressed as the % DNA peak size exclusion. The effects caused by the antitumor drugs melphalan, busulphan, and busulpan analogues on DNA were clearly observed through chromatographic data. The synthetic dimethanesulphonates of 2-tetradecyl-1,4-butanediol and 1,2-hexadecanediol were proved more potent than busulphan.